Nadir bir akut karın sebebi: Omental torsiyon - Yılmaz, Ahmet; Atak, Tuba; Bozkurt, Süleyman; Bayraktar, Barış; Sağıroğlu, Julide (Yerküre Tanıtım & Yayıncılık Hizmetleri, 2015)
Omental torsiyon nadir görülen bir akut karın nedeni olup klinik olarak birçok hastalığı taklit edebilmektedir. Tanı ve tedavisinde laparoskopi son derece yararlı bir yöntemdir. Bu yazıda, diagnostik laparoskopide omentumun torsiyonu tespit edilen ve laparoskopik olarak nekroze omentum dokusunun rezeke edildiği bir olgu sunulmaktadır.

Omental torsion is a rare cause of acute abdominal pain and can mimic clinically many diseases. Laparoscopy is a useful method in the diagnosis and treatment of the omental torsion. In this article, a case with omental torsion which was detected during diagnostic laparoscopy and the necrosed omental tissue resection was done laparoscopically has been presented.
A rare cause of acute abdomen: The omental torsion
WOS: 000364167800007
Keywords: Akut Karın; Omental Torsiyon; Acute Abdomen; Omental Torsion